2018
DOI: 10.1016/j.bbi.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and interleukin (IL)-6 concentrations across pregnancy among Mexican-American women

Abstract: Maternal inflammation during pregnancy may represent a biological pathway of interest in the context of the inter-generational effects of acculturation from a mother to her as-yet-unborn child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
1
18
0
3
Order By: Relevance
“…These findings may be due in part to cumulative (and potentially intergenerational) exposure to discrimination during the acculturation process (131)(132)(133). Studies have also identified a relationship between greater acculturation and blunted maternal cortisol response (134) in addition to elevated concentrations of the inflammatory cytokine interleukin-6 (135), which may be biological mechanisms through which acculturation has an impact on adverse birth outcomes. Overall, these findings suggest that racial and ethnic disparities in the rates of obstetric complications in the United States could contribute to a developmental trajectory toward psychosis and findings of higher schizophrenia rates among Black individuals, immigrant populations, and potentially other less studied groups that experience high discrimination rates (e.g., because of religion, sexuality, and other racial and ethnic identities).…”
Section: Racial Disparities During Pre-and Perinatal Periodsmentioning
confidence: 99%
“…These findings may be due in part to cumulative (and potentially intergenerational) exposure to discrimination during the acculturation process (131)(132)(133). Studies have also identified a relationship between greater acculturation and blunted maternal cortisol response (134) in addition to elevated concentrations of the inflammatory cytokine interleukin-6 (135), which may be biological mechanisms through which acculturation has an impact on adverse birth outcomes. Overall, these findings suggest that racial and ethnic disparities in the rates of obstetric complications in the United States could contribute to a developmental trajectory toward psychosis and findings of higher schizophrenia rates among Black individuals, immigrant populations, and potentially other less studied groups that experience high discrimination rates (e.g., because of religion, sexuality, and other racial and ethnic identities).…”
Section: Racial Disparities During Pre-and Perinatal Periodsmentioning
confidence: 99%
“…IL-6 mediates embryo implantation and placental development [ 63 ]. Maternal serum IL-6 concentrations significantly increase during healthy pregnancy [ 64 ]. Others also reported significantly higher IL-6 concentrations in the third trimester in comparison to samples collected earlier in pregnancy [ 35 , 59 , 65 , 66 ].…”
Section: Cytokines In Healthy Pregnancymentioning
confidence: 99%
“…Given these health disparities, research has identified risk factors that contribute to Latina's experience of psychological distress (Ayón, 2015). Higher levels of acculturation (i.e., the process of adapting to host country values, practices, and beliefs and/or losing cultural heritage) (Berry, 1997;Schwartz et al, 2010) in Latina mothers has been associated with higher levels of prenatal (Ruiz et al, 2007) and postpartum (Alhasanat and Giurgescu, 2017) depressive symptoms and worsened prenatal neuroendocrine and immune profiles associated with chronic stress (D'Anna-Hernandez et al, 2012;Ruiz et al, 2006;Scholaske et al, 2018;Wommack et al, 2013). In fact, acculturative-related processes have been implicated in the postmigration intergenerational transmission of health disparities in Latinas (Fox et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Economic hardship, a universal stressor, is both a well-established risk factor for prenatal depression (Lancaster et al, 2010) and a culturally relevant stressor, considering that 26% of Latino families live in poverty (U.S. Census Bureau, 2017). Some research suggests that lower income heightens the relationship between acculturative stress and psychological distress in immigrant Latinas (Bekteshi and van Hook, 2015), whereas other research suggests that the relationship between adverse prenatal immune profiles and acculturation is not moderated by income (Scholaske et al, 2018). As such, the extent to which economic hardship in Latinas may be associated with prenatal depressive and anxiety symptoms and biological profiles in relation to other psychosocial stressors remains less understood.…”
Section: Introductionmentioning
confidence: 99%